Blood Pressure Tracking From Childhood to Adulthood - Azegami, Tatsuhiko; Uchida, Keiko; Tokumura, Mitsuaki; Mori, Masaaki (Frontiers in Pediatrics, 2021)
Hypertension is the most common non-communicable disease among adults and is the most important modifiable risk factor for premature cardiovascular disease. The increasing worldwide burden of hypertension is a major global health issue. Early prevention with lifestyle modification or pharmaceutical treatment reduces the incidence of hypertension and the risk of subsequent cardiovascular disease. Therefore, identification of young persons at risk for hypertension has the obvious benefit of providing a chance for early intervention. Previous studies have demonstrated the positive association of elevated childhood blood pressure with hypertension in adulthood. Accumulated evidence also indicates the possibility that elevated pediatric blood pressure is associated with increased risk of future cardiovascular disease. In this article, we review the tracking of blood pressure from childhood to adulthood and emphasize the importance of pediatric blood pressure monitoring and control for predicting and preventing adult hypertension and cardiovascular disease.